2017
DOI: 10.3390/ijms18040721
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling Comparing the Effects of Different Heat Treatments on Camel (Camelus dromedarius) Milk Whey Proteins

Abstract: Camel milk is consumed in the Middle East because of its high nutritional value. Traditional heating methods and the duration of heating affect the protein content and nutritional quality of the milk. We examined the denaturation of whey proteins in camel milk by assessing the effects of temperature on the whey protein profile at room temperature (RT), moderate heating at 63 °C, and at 98 °C, for 1 h. The qualitative and quantitative variations in the whey proteins before and after heat treatments were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Furthermore, CM whey proteins were also reported to be more sensitive to heat treatments, with denaturation rates faster than those of bovine milk (Felfoul, Lopez, Gaucheron, Attia, & Ayadi, 2015a). Benabdelkamel et al (2017) indicated that heat treatment of CM whey at 98 °C for 60 min caused a significant denaturation of camel α-lactalbumin (α-la), lactoferrin (LF), and serum albumin (SA).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CM whey proteins were also reported to be more sensitive to heat treatments, with denaturation rates faster than those of bovine milk (Felfoul, Lopez, Gaucheron, Attia, & Ayadi, 2015a). Benabdelkamel et al (2017) indicated that heat treatment of CM whey at 98 °C for 60 min caused a significant denaturation of camel α-lactalbumin (α-la), lactoferrin (LF), and serum albumin (SA).…”
Section: Introductionmentioning
confidence: 99%
“…The gels were scanned with a Typhoon 9400 scanner using appropriate wavelengths and filters for Cy2, Cy3 and Cy5. Difference in-gel electrophoresis (DIGE) images were analyzed using the Progenesis SameSpots v.3.3 software (Nonlinear Dynamics Ltd., UK) as described previously 53 . All spots were pre-filtered and manually checked before applying the statistical criteria (ANOVA test, p ≤ 0.05 and fold ≥ 1.5).…”
Section: Resultsmentioning
confidence: 99%
“…The extraction of MFGM was done as described previously [75,76] with some modifications. Briefly, the MFGM pellets were incubated with lysis buffer (pH 8.8, 30 Mm Tris buffer containing 7 M urea, 2 M thiourea, 2% Chaps, 1× protease inhibitor mix), for 1 h with periodic vortexing.…”
Section: Extraction Of Mfgm Proteinsmentioning
confidence: 99%
“…Coomassie-stained gel spots from the preparatory gel were washed and digested according to previously described methods [76][77][78]. The mixture of tryptic peptides (1 µL) derived from each protein was spotted onto a MALDI target (384 Anchorchip MTP 800 µm Anchorchip; Bruker Daltonik, Bremen, Germany).…”
Section: Protein Identification By Maldi-tof Msmentioning
confidence: 99%